2018
DOI: 10.18632/oncotarget.25209
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative oncology DNA sequencing of canine T cell lymphoma via human hotspot panel

Abstract: T-cell lymphoma (TCL) is an uncommon and aggressive form of human cancer. Lymphoma is the most common hematopoietic tumor in canines (companion animals), with TCL representing approximately 30% of diagnoses. Collectively, the canine is an appealing model for cancer research given the spontaneous occurrence of cancer, intact immune system, and phytogenetic proximity to humans. We sought to establish mutational congruence of the canine with known human TCL mutations in order to identify potential actionable onco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 42 publications
(53 reference statements)
1
19
0
Order By: Relevance
“…The global gene expression pattern was consistent with downregulation of PTEN and upregulation of the PI3K/AKT and mTOR pathways. This finding supports previous studies that have identified mutations in PTEN in canine TCL . Variant analysis of RNA transcripts identified a silent single nucleotide polymorphism in the PTEN transcript in one of the six sequenced PTCL samples.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The global gene expression pattern was consistent with downregulation of PTEN and upregulation of the PI3K/AKT and mTOR pathways. This finding supports previous studies that have identified mutations in PTEN in canine TCL . Variant analysis of RNA transcripts identified a silent single nucleotide polymorphism in the PTEN transcript in one of the six sequenced PTCL samples.…”
Section: Discussionsupporting
confidence: 91%
“…A recent study used a Human Cancer Hotspot Panel to identify potential tumour-associated mutations in canine PTCL. 36 MET, KDR, STK11, and BRAF were highly mutated and missense mutations were identified in MYC, TP53, and MET. In our study, a synonymous mutation in the promoter region of MYC and synonymous mutations in exons of KDR were present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The canine model of cancer is considered an excellent model for human translation [66][67][68][69]. Thus, we employed companion canines recruited to the Western College of Veterinary Medicine at the University of Saskatchewan with treatment resistant lymphoma into our study to reveal the gene expression differences between tumors with variable treatment responsivenesses, as well as to determine the effects of metformin on cancer progression in these animals.…”
Section: Discussionmentioning
confidence: 99%
“…Our proximity to the largest Veterinary College in western Canada provided us an opportunity to obtain treatment resistant tumor samples representative of in vivo events as companion dogs present regularly to the oncology clinic for diagnosis and chemotherapy. Canine lymphoma is orthologous to non-Hodgkin lymphoma of B-and T-cells and has a relapsing-remitting course with a high incidence of terminal MDR transformation [33][34][35]. The superficial nature of the lymph node enlargements allows easy access to tumor sampling in a non-invasive manner.…”
Section: Companion Canines With Non-hodgkin-like Lymphoma Are Strong mentioning
confidence: 99%